Assessing damage mitigation by silanized milled graphite nanoparticles in hybrid GFRP laminated composites. (May 2020) - Das, Subhankar; Halder, Sudipta; Khan, Nazrul Islam; Paul, Bappi; Goyat, M.S.
Abstract: In GFRP laminated composites, matrix-fiber delamination is almost unavoidable and a serious problem that significantly hampers the mechanical properties of the composites. This work presents the use of cost-effective silanized milled graphite nanoparticles (GrNPs) to mitigate matrix-fiber delamination in GFRP laminated composites. FESEM and TEM analysis of pristine GrNPs exhibit porous structure consisting of stacked and randomly oriented planes with a large number of defect sites. The silanization of GrNPs (SGrNPs) results in the covering of pores or defect sites and produces the rough surfaces. The SGrNPs (0.5 wt%) reinforced GRFP laminated composites reveal the enhancement in the mechanical properties such as tensile strength ( 33%), tensile modulus ( 21%), toughness ( 35%), flexural strength ( 42.6%), work of fracture ( 57%), and short beam strength ( 23%), respectively. The improvement in the mechanical properties of the composites is due to the mitigation of matrix-fiber delamination by SGrNPs.